Executive tasks and cognitive flexibility and their relationship to academic achievement among university students with attention deficit hyperactivity disorder - Jawzaa H Almutairi; Abeer T Ahmed (Wolters Kluwer Medknow Publications, 2022)
Background: The current study measured the executive tasks and cognitive flexibility and their relationship to the academic achievement of female students of the College of Education at Imam Abdulrahman Bin Faisal University in the Kingdom of Saudi Arabia. Materials and Methods: This research is a descriptive quantitative design. The study sample included 200 female students using purposive sampling. The study applied a test of executive tasks, cognitive flexibility, and a scale of attention deficit hyperactivity disorder for adults prepared by the researchers. Data were analyzed using several tests, namely descriptive statistics, Pearson correlation at the level of <0.05. Results: The results showed a statistically significant relationship between the scores of students with attention deficit and hyperactivity on the executive tasks scale and its dimensions (planning, organization, purposeful action, self-monitoring, and total score), cognitive flexibility, and academic achievement, which necessitates the need to design empirical research to reduce the severity of attention deficit hyperactivity disorder among undergraduate students because it will have a positive impact on their academic achievement. Conclusion: The researchers highlight the necessity for conducting empirical research to improve the executive tasks of students as it will have a positive impact on their lives.